THE INFLUENCE OF B-CYCLODEXTRIN CONCENTRATIONS AS LIGANDS ON INCLUSION COMPLEXES TO INCREASE THE SOLUBILITY OF IBUPROFEN - Rahmah Elfiyani; Anisa Amalia; Alvin Integra (Sanata Dharma University, 2020)
Ibuprofen is a compound with low solubility but high permeability in water. One method to improve the ability of a substance to dissolve in water is through the formation of inclusion complexes. This study aims to obtain ratio between ibuprofen and b-cyclodextrin which results in inclusion complex with an optimal amount of dissolved ibuprofen. The inclusion complex was made using solvent evaporation method with molar ratio variations of 1: 1, 1: 2, 1: 3, 1: 4 and 1: 5. The results of the inclusion complex were characterized by X-ray diffraction, FTIR, SEM, and DTA. The solubility test was carried out using three different media; they are pH solution 7.4; pH solution 1.5; and distilled water. The solubility test results showed no increase on the ibuprofen solubility of the inclusion complex within medium solutions of pH 7.4 and pH 1.5 whereas in aquades medium there was an increase in the inclusion complex solubility compared to pure ibuprofen. Based on the results, it can be concluded that inclusion complex with molar ratio of 1: 1 shows optimal amount of dissolved ibuprofen compared to other ratio variations in aquadest medium.